Discussion of the deification of the human person and the role of technology in Eastern-Orthodox Christianity - Hermanni, Friedrich 1958- (2001)
In response to a question from Brumlik about how “deification” is to be understood, Horuzhy answered that this is an idea of the Eastern Orthodox discourse and must be understood as the perfect connection of all human energies with the divine energy. The divine energy indeed comes from another mode of being, another ontological horizon, but is nevertheless present in the human horizon. This is the theological definition and it is amplified by a physical parallel: The human person must put himself in a particular state in order to attain contact with the external energy of God. This contact between the ontological energies is called “synergy.”